Perfluorochemical Liquid-Adenovirus Suspensions Enhance Gene Delivery to the Distal Lung - Kazzaz, Jeffrey A.; Strayer, Marlene S.; Wu, Jichuan; Malone, Daniel J.; Koo, Hshi-chi; Shaffer, Thomas H.; Davis, Jonathan M.; Strayer, David S.; Wolfson, Marla R. (Pulmonary Medicine, 2011)
We compared lung delivery methods of recombinant adenovirus (rAd): (1) rAd suspended in saline, (2) rAd suspended in saline followed by a pulse-chase of a perfluorochemical (PFC) liquid mixture, and (3) a PFC-rAd suspension. Cell uptake, distribution, and temporal expression of rAd were examined using A549 cells, a murine model using luciferase bioluminescence, and histological analyses. Relative to saline, a 4X increase in transduction efficiency was observed in A549 cells exposed to PFC-rAd for 2–4 h. rAd transgene expression was improved in alveolar epithelial cells, and the level and distribution of luciferase expression when delivered in PFC-rAd suspensions consistently peaked at 24 h. These results demonstrate that PFC-rAd suspensions improve distribution and enhance rAd-mediated gene expression which has important implications in improving lung function by gene therapy.